Overcoming Workplace Conflicts in Multicultural Organizations: Conflict Factors and Resolution Strategies - Hussain, Haider Rifaat; Kim, Ji Young (Semantik: Journal of Social, Media, Communication, and Journalism, 2025)
In todayÔÇÖs globalized society, working environment has become diverse and organizations face both, opportunities and challenges based on the cultural differences of their workforce. The U.S. is one of many countries experiencing expansion in workplace diversity. In 2019, a majority of new hires in the U.S. were people of color between the ages 25 to 54 (Long & Damn, 2021). The report shows that the Latin population may constitute 20% of AmericaÔÇÖs workforce by the year 2028 (Long & Damn, 2021). Also, Blacks and Asians constituted 19% of the total labor force of the U.S. in 2020 (U.S. Bureau of Labor Statistics, 2021).┬á This workforce diversity increases our attention to the cultural differences experienced in workplace settings and its impact organizational communication and performance. Employees experience many cultural challenges, and without proper cross-cultural adjustment, their level of work stress may increase (Chen, 2019). Also, cultural diversity can lead to intercultural conflicts in the workplace. Scholars defined intercultural conflict as ÔÇ£different expectations concerning appropriate or inappropriate conflict behavior in a conflict sceneÔÇØ (Ting-Toomey & Oetzel, 2001, p. 1). Organizations try to manage those conflicts through effective communication and cultural trainings (Shahid, 2022). The purpose of this study is to unearth causes of workplace conflicts through in-depth interviews of employees across culturally diverse organizations in the United States, and to identify ways to reduce these cultural gaps and increase intercultural understanding among employees. Findings of this study will bridge existing gaps in literature and help organizations prepare and implement a course of action that builds a harmonious and collaborative workplace culture